A randomised controlled trial of intrapleural balloon intercostal chest drains to prevent drain displacement. Issue 1 (21st July 2022) - Mercer, Rachel M.; Mishra, Eleanor; Banka, Radhika; Corcoran, John P.; Daneshvar, Cyrus; Panchal, Rakesh K.; Saba, Tarek; Caswell, Melanie; Johnstone, Sarah; Menzies, Daniel; Ahmer, Sana; Shahidi, Mitra; et al.
Background: Chest drain displacement is a common clinical problem that occurs in 9–42% of cases and results in treatment failure or additional pleural procedures conferring unnecessary risk. A novel chest drain with an integrated intrapleural balloon may reduce the risk of displacement. Methods: A prospective randomised controlled trial comparing the balloon drain to standard care (12 F chest drain with no balloon) with the primary outcome of objectively defined unintentional or accidental chest drain displacement. Results: 267 patients were randomised (primary outcome data available in 257, 96.2%). Displacement occurred less frequently using the balloon drain (displacement 5 of 128, 3.9%; standard care displacement 13 of 129, 10.1%) but this was not statistically significant (OR for drain displacement 0.36, 95% CI 0.13–1.0, Chi-squared 1 degree of freedom (df)=2.87, p=0.09). Adjusted analysis to account for minimisation factors and use of drain sutures demonstrated balloon drains were independently associated with reduced drain fall-out rate (adjusted OR 0.27, 95% CI 0.08–0.87, p=0.028). Adverse events were higher in the balloon arm than the standard care arm (balloon drain 59 of 131, 45.0%; standard care 18 of 132, 13.6%; Chi-squared 1 df=31.3, p<0.0001). Conclusion: Balloon drains reduce displacement compared with standard drains independent of the use of sutures but are associated with increased adverse events specifically during drain removal. The potential benefits of the novel drain should be weighed against the risks, but may be considered in practices where sutures are not routinely used. Results show that an intrapleural balloon is beneficial in preventing chest drain displacement, even when accounting for the use of chest drain sutures, but this was associated with minor difficulties with insertion and removal https://bit.ly/31fm7fB